Factor Inhibitor Game Traditional in Public Elementary Schools in the District Shotgun - Apriani, Leni; Alpen , Joni; Yulianti , Mimi; Wijaya , Chandra; Syaputra , Rian Amanda (Indonesian Journal of Sport Management, 2024)
Traditional games are one of the physical education materials, namely all actions, whether using tools or not, passed down from generation to generation from ancestors, as a means of entertainment or to please the heart. The aim is to awaken and grow the characters of elementary school children. The research method used by researchers is a qualitative approach with descriptive methods. Data collection techniques in qualitative research are conducted through observations, interviews, and documentation studies. The population and sample for this research were 10 PJOK teachers in the Senapelan sub-district. Based on the study results and discussion, the conclusion is that inhibiting factors support the lack of traditional games in elementary schools in the city of Pekanbaru, one of the elementary schools in the Senapelan sub-district. In the K13 curriculum, there is still traditional game learning, whereas in the MBKM curriculum, learning has not been implemented or taught in any of the traditional game learning. These 10 schools still use the 2 K13 and MBKM curricula. Therefore, there is not an even level in every lesson in the curriculum regarding these traditional games. So, knowledge of traditional games is given to children, so there needs to be more activity in these traditional games.